Hubungan Usia Gestasi, Jenis Persalinan, Infeksi dan Inisiasi Menyusu Dini dengan Derajat Hiperbilirubinemia Neonatus - Dian Rohmah; Hari Ghanesia Istiani (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2026)
Neonatal hyperbilirubinemia may progress to acute bilirubin encephalopathy and permanent neurological injury when risk factors are not recognized promptly. This study examined the relationships of gestational age, delivery type, neonatal infection, and early breastfeeding initiation with hyperbilirubinemia severity among neonates treated in a neonatal intensive care unit. A retrospective analytic study used complete medical records of 179 neonates with hyperbilirubinemia admitted to the NICU of Grha Permata Ibu Hospital from July 2024 to June 2025. Total sampling was applied. Hyperbilirubinemia severity, gestational age, delivery type, infection status, and early breastfeeding initiation were extracted using a structured observation sheet. Data were analyzed using frequency distributions, chi-square tests, and Cramer’s V at a 5% significance level. Most neonates had grade 3 hyperbilirubinemia (42.5%), were born at term (84.4%), delivered by cesarean section (91.1%), had no documented infection (63.7%), and did not receive early breastfeeding initiation (53.1%). Severity was significantly associated with gestational age (p = .007; V = .236), infection (p < .001; V = .307), and early breastfeeding initiation (p = .002; V = .259), but not with delivery type (p = .233; V = .128). Risk-oriented neonatal nursing should prioritize preterm infants, early infection identification, and timely breastfeeding support while maintaining bilirubin surveillance based on postnatal age and clinical risk.